(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
The highly dynamic nature of MANETs results in frequent and unpredictable changes in the network topology, which add to the difficulty and complexity to routing among the mobile nodes within the network. Thus, establishing communication among mobile nodes is a great challenge in itself, resulting in network overloading & discarding of data packets. Nodes can change position quite frequently, which means we need a routing protocol that quickly adapts to the topology changes which is our objective. Â In this paper focus has been put on the strategy to address the packet drop ratio which is an integral and important factor of communication in MANETs by minimizing the request zone. In Mobile Ad-Hoc Networks, as the coverage area increases the packet drop ratio also increases which degrades the network performance and Quality of Service (QOS).Location Aware Routing Â will be used as a base protocol for the proposed work which is a class of Reactive protocol to design optimized routing algorithm.